Livestock diversity in shifting cultivation area of North Eastern Hill states in India - PANDEY, D K; DE, H K; MISHRA, B K; KUMAR, PRABHAT; BIAM, KAMNI PAIA (The Indian Journal of Animal Sciences, 2019)
The breed of animals and birds reared by the jhumia were mostly non-descript and the method of rearing was traditional or backyard farming. Local breeds are an important self-replicating asset of almost all jhumia people and fulfill functions that go far beyond the output of products. At one end of the spectrum are breeding and production systems in which animals are kept in natural environments and are exposed to a large degree of natural selections imposed by the elements. Such systems are prevalent in ecologically marginal areas and typically practiced by pastoralists for whom adaptation traits are more crucial than production traits. Considering the distinctive features of animal genetic resources, as well as the urgent need for maintaining and conserving domestic animal diversity for future generations, it is necessary to promote more productive and sustainable livestock management.